The Modification of the Probation Period as an Effect of Transposing the Directive (Eu) 2019/1152 in the Romanian Law - Știrbu , Gabriela Petruța; Stoian, Nicolae Radu (Journal of Legal Studies, 2025)
Directive 2019/1152 has brought to the forefront the importance of the probationary period in an employment relationship, by its dual importance both in the activity of an enterprise by enabling the employer to find workers as competent as possible for the performance of the activity, and for the worker, who has the opportunity to know from the beginning of the employment relationship what conditions he must fulfill. Law no. 283/2022 amended the national law in the sense that it made it mandatory to expressly mention the conditions of the probationary period, if any, thus creating a conflict between the existing rules, in relation to the fact that during the probationary period, there is the possibility of termination of the individual employment contract by a simple unjustified notification by either party. In the following study, we will try to solve the legal problem of whether there or there is not a change in the legislator’s optics regarding the reasons for the termination of the individual employment contract during the probationary period.